(untitled) (Journal of Social Sciences Review, 2025)
The current research study discovers the stylistic features in Samuel Taylor Coleridge’s select stanzas of the poems–Kubla Khan, The Eolian Harp, and Fears in Solitude, with particular consideration to key ideas of the supernatural and religion. By using a stylistic approach, the current paper examines how Coleridge’s use of imagery, diction, rhythm, and syntax guides the mystical and spiritual dimensions of his verse. As Brumfit and Carter (1986) observe, “Poetry offers a unique field for stylistic exploration, where the density of linguistic features amplifies the interpretive possibilities” (p. 21). This analysis validates how Coleridge’s poetic language enhances both meaning and reader experience through its stylistic richness. In sum, the paper contributes to the new dimensions explored pertaining to religion and supernatural specifically in the broader domain of stylistic studies.